2016
DOI: 10.1016/j.juro.2015.10.130
|View full text |Cite
|
Sign up to set email alerts
|

Could Testosterone Replacement Therapy in Hypogonadal Men Ameliorate Anemia, a Cardiovascular Risk Factor? An Observational, 54-Week Cumulative Registry Study

Abstract: After 54 weeks testosterone undecanoate decreased the prevalence of anemia and components of the metabolic syndrome. A longer duration of testosterone undecanoate therapy of more than 18 weeks may be effective and safe in reducing blood viscosity and improving anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Although men with testosterone deficiency are not always diagnosed with anemia, the relationship between testosterone deficiency and low hemoglobin is significant, suggesting that low testosterone is one of the causal factors of anemia. Zhang et al [31] investigated the effects of testosterone treatment in 58 patients with testosterone levels <235 ng/dL and mild symptoms of testosterone deficiency. Hb, hematocrit, anemia risk factors, whole blood viscosity, and anthropometrics were measured.…”
Section: Impact Of Testosterone Deficiency and Testosterone Treatmentmentioning
confidence: 99%
“…Although men with testosterone deficiency are not always diagnosed with anemia, the relationship between testosterone deficiency and low hemoglobin is significant, suggesting that low testosterone is one of the causal factors of anemia. Zhang et al [31] investigated the effects of testosterone treatment in 58 patients with testosterone levels <235 ng/dL and mild symptoms of testosterone deficiency. Hb, hematocrit, anemia risk factors, whole blood viscosity, and anthropometrics were measured.…”
Section: Impact Of Testosterone Deficiency and Testosterone Treatmentmentioning
confidence: 99%
“…Thirty‐one Caucasians (age: median [IQR] 55.0 years [49.0‐68.0]; total duration of follow‐up 6.1 years [2.9‐9.3]) and 19 South Asians (age: 52.0 years [38.0‐69.0]; duration of follow‐up 6.5 years [1.3‐8.4]) were treated with TU during the study period (see Table ). On average, the Caucasian group had 18 injection treatments compared with the South Asian group who had 16 injection treatments . This was not significantly different between the groups ( P = .3993).…”
Section: Resultsmentioning
confidence: 82%
“…Both ethnic groups returned to their baseline levels over the eight years. Jones et al reported the risk of erythrocytosis following TRT could be attributed to EPO production, bone marrow stimulation and increased iron bioavailability with higher risk with intramuscular therapy . Zhang et al found that TU therapy significantly increased haematocrit and haemoglobin in a cohort of 1221 ageing men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the potential increased risk of VTE, one theorized mechanism is that testosterone induces polycythemia, which increases blood viscosity [3]. Interestingly, another recent nonrandomized single‐center open‐label registry study supports the possibility that longer duration testosterone replacement therapy (TRT) in testosterone deficient males may decrease the prevalence of anemia, improve lipid profiles, and may actually lower the overall risk for VTE [4]. When considering the effects of TRT administration, one must consider the overall need and goals of therapy, duration of treatment, and the patient's comorbidities.…”
mentioning
confidence: 99%